2011
DOI: 10.4314/pamj.v9i1.71201
|View full text |Cite
|
Sign up to set email alerts
|

Health effects of agrochemicals among farm workers in commercial farms of Kwekwe district, Zimbabwe

Abstract: IntroductionFarm workers are at a very high risk of occupational diseases due to exposure to pesticides resulting from inadequate education, training and safety systems. The farm worker spends a lot of time exposed to these harmful agrochemicals. Numerous acute cases with symptoms typical of agrochemical exposure were reported from the commercial farms. We assessed the health effects of agrochemicals in farm workers in commercial farms of Kwekwe District (Zimbabwe), in 2006.MethodsAn analytical cross sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 9 publications
(7 reference statements)
6
39
2
1
Order By: Relevance
“…The results showed that slightly more than half of the respondents used a face cover and gumboots, and fewer than half wore overalls, when using pesticides. Magauzi et al 15 reported that low provision of protective clothing was a major risk factor for pesticide poisoning among farm workers in Zimbabwe. In many African countries, poor utilisation of protective clothing is a serious problem among small-scale farmers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that slightly more than half of the respondents used a face cover and gumboots, and fewer than half wore overalls, when using pesticides. Magauzi et al 15 reported that low provision of protective clothing was a major risk factor for pesticide poisoning among farm workers in Zimbabwe. In many African countries, poor utilisation of protective clothing is a serious problem among small-scale farmers.…”
Section: Resultsmentioning
confidence: 99%
“…A study among farm workers in Zimbabwe 15 showed that ignorance of colour codes was a major problem and a risk factor for pesticide exposure. Understanding colour coding on pesticide containers is therefore important to prevent pesticide poisoning.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, there is scant information on the details of health effects and costs related to pesticide exposure, as most cases go unreported [28,60,61]. However, Magauzi et al [63] reported high organophosphate levels in young horticultural farmworkers' blood and also recorded 24.1% abnormal cholinesterase activity in 50% of the sprayers (occupational exposure) and 49% of workers entering previously sprayed fields (non-occupational exposure) in Zimbabwe. Khoza et al [64] reported similar results with both organophosphates and organochlorines and further reported chronic illnesses that were often misdiagnosed and mistreated in health centres; possibly due to rampant pesticide incorrect use [65].…”
Section: Farmers' Behaviour and Insecticide Usementioning
confidence: 99%
“…Such hazardous compounds, even when geographically concentrated in pattern, could create significant exposure to the environment and the public through non-occupational exposure, where individuals not directly involved with chemical use get exposed to the chemical hazards through a contaminated environment [61,62]. Magauzi et al [63] and Macharia et al [28] detailed pesticide-related illnesses in Zimbabwe and Kenya respectively, and it has been reported that various symptoms related to pesticide poisoning have significantly increased as most small-scale farmers misuse chemicals and do not use personal protective equipment (PPE) [64]. Moreover farmers tend to ignore or take for granted certain levels of illnesses from synthetic chemicals, which they feel do not warrant medical attention, as an expected normal part of farmwork [60].…”
Section: Farmers' Behaviour and Insecticide Usementioning
confidence: 99%
“…Being provided with face masks was also found to be a significant risk factor. This might mean that the type of PPE used was either inappropriate or was not being used properly (15). Literacy and inadequate awareness may be a part of the problem, as the majority of the study participants had limited education.…”
Section: Discussionmentioning
confidence: 99%